2020
DOI: 10.5433/1679-0359.2020v41n6p2655
|View full text |Cite
|
Sign up to set email alerts
|

Semina: Ciências Agrárias USER You are logged in as... seminagra My Journals My Profile Log Out LANGUAGE Select Language English JOURNAL CONTENT Search Search Scope All Browse By Issue By Author By Title Other Journals FONT SIZE INFORMATION For Readers For Authors For Librarians Journal Help OPEN JOURNAL SYSTEMS HOME ABOUT USER HOME SEARCH CURRENT ARCHIVES AUTHOR GUIDELINE REGISTER INDEXERS JOURNALS PORTAL UEL Home > Vol 41, No 6 (2020) > Barnabé Assessment of caseous lymphadenitis in goats in a s

Abstract: Caseous lymphadenitis (CLA) caused by the pathogenic bacterium, Corynebacterium pseudotuberculosis, results in economic loss in goat farming. Its prevalence in Brazilian herds varies from 5 to 50%, generating expenses with treatment, loss in production, carcass and organ condemnation, and reduced price of the hide. This study aimed to describe the distribution of lesions and quantify the loss associated with CLA in goat breeding due to condemnation in a slaughterhouse located in a semiarid region. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…The distribution of CLA at the farm level was 56.36%, suggesting that more than half of the farms had at least one CLA-positive goat. Epidemiological studies in other countries that performed clinical examinations to identify CLA prevalence included studies in Brazil (25.33%) ( 22 ), Egypt (11.04%) ( 15 ), two separate studies in Ethiopia (18.80 and 15.00%) ( 8 , 16 ), and India (4.38%) ( 23 ). The differences in CLA prevalence between different studies may be attributed to the variation in management systems and climatic conditions in each study, as the viability of the causative organism in the contaminated environment is greatly affected by ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of CLA at the farm level was 56.36%, suggesting that more than half of the farms had at least one CLA-positive goat. Epidemiological studies in other countries that performed clinical examinations to identify CLA prevalence included studies in Brazil (25.33%) ( 22 ), Egypt (11.04%) ( 15 ), two separate studies in Ethiopia (18.80 and 15.00%) ( 8 , 16 ), and India (4.38%) ( 23 ). The differences in CLA prevalence between different studies may be attributed to the variation in management systems and climatic conditions in each study, as the viability of the causative organism in the contaminated environment is greatly affected by ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…They may also be attributed to the endemic nature of the disease, which leads to variations in animal immunity and degree of animal susceptibility ( 15 ). Furthermore, variations in the use of different diagnostic tools for determining CLA may contribute to differences in CLA prevalence among different countries ( 8 , 16 , 22 ). In the present study, CLA lesions were detected through direct examination of the carcass, and the etiology of the lesions was confirmed using PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da caprinocultura ser uma atividade econômica de grande importância do agronegócio brasileiro, principalmente em localidades onde há grande presença de pequenos produtores, ainda há falta de adoção de tecnologias (SAMPAIO et al, 2009). Aliado a este fator, observa-se um manejo sanitário deficitário, o que acaba contribuindo para uma baixa produtividade, tendo em vista a disseminação de algumas doenças que prejudicam a cadeia de produção (BARNABÉ et al, 2020).…”
Section: Introductionunclassified
“…In Australia, where financial losses related to this disease have been extensively studied, CLA causes an estimated annual loss of $12-$15 million to the meat industry and approximately a $17 million annual loss in wool production (Osman et al 2018). In Brazil, data from a study aiming at determining the negative impact of CLA in a slaughterhouse revealed economic losses of 6.09% on goat production (Barnabé et al 2020). Currently, commercially available vaccines for Corynebacterium pseudotuberculosis demonstrate limited efficacy and do not provide effective protection against CLA.…”
Section: Introductionmentioning
confidence: 99%